PRINCIPALLY QUASI DUAL-BAER MODULES - Kumar S.; Gupta A.J. (My University, 2025)
In this paper, we generalize quasi dual-Baer module to principally quasi dual-Baer (PQ dual-Baer) module. A module M is said to be PQ dual-Baer if for each cyclic submodule X of M, DE(X) = {f ∈ E: Im(f) ⊆ X} is a direct summand of E = End(M). We study some properties of PQ dual-Baer modules. We find some conditions for which the direct sum of arbitrary copies of PQ dual-Baer modules is PQ dual-Baer. We also study the ring of endomorphisms of PQ dual-Baer modules. © Palestine Polytechnic University-PPU 2023.